1995
DOI: 10.1017/s1041610295002195
|View full text |Cite
|
Sign up to set email alerts
|

Agitation Among Elderly Persons at Adult Day-Care Centers: The Experiences of Relatives and Staff Members

Abstract: Two hundred participants (mean age = 80 years) from five senior day-care centers were included in a study of agitation. Staff members at the centers and participants' relatives rated the frequency with which participants displayed agitated behaviors, via an expanded version of the Cohen-Mansfield Agitation Inventory. The most frequent behaviors noted were general restlessness, repetitious sentences, verbal interruptions, and pacing. A three-factor solution for staff members' ratings included (a) physically non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
92
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 107 publications
(101 citation statements)
references
References 8 publications
8
92
1
Order By: Relevance
“…Most of the participants (86.5%) were Caucasian. The participants' demographic data were similar to those of the participants in a national survey of day care users although a greater proportion of the participants in this study were Caucasian as compared to the national survey and a greater proportion was disabled in the performance of ADL (3).…”
Section: Participantssupporting
confidence: 57%
“…Most of the participants (86.5%) were Caucasian. The participants' demographic data were similar to those of the participants in a national survey of day care users although a greater proportion of the participants in this study were Caucasian as compared to the national survey and a greater proportion was disabled in the performance of ADL (3).…”
Section: Participantssupporting
confidence: 57%
“…phrases). Subsequent research involving factor analysis led to the refinement of these syndromes by subdividing verbally agitated behaviors into: verbally aggressive (i.e., cursing) and verbally nonaggressive behaviors (i.e., negativism) [17]. However, there remains a strong interrelationship between these subdivisions [18].…”
Section: Introductionmentioning
confidence: 99%
“…To achieve the goal, the study was conducted based on the background and proximal factors of the need-driven behavior model 19 developed to explain the causes of agitation in dementia patients. Regarding physical agitation, Cohen-Mansfield et al [34] showed cognitive function decreases with increasing physical non-aggressive behavior. Gang et al [10] did not find the effect of cognitive function on physical agitation, but found that the duration of dementia, visual acuity, sleep quality, and physiological discomfort influenced physical agitation.…”
Section: Discussionmentioning
confidence: 99%